Pengaruh Social Media Marketing Instagram dan Electronic Word Of Mouth Terhadap Keputusan Pembelian di Cafe Gartenhutte Mojokerto - Dewi Jaiz Siangsari; Rena Feri Wijayanti (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
Mojokerto's Gartenhutte Cafe is one of the recommended cafes which is considered a contemporary place to relax with a hidden gem concept. To introduce its products to consumers, the Gartenhutte cafe uses Instagram as its marketing social media and also carries out electronic word of mouth promotions. Research was conducted to determine the impact of Instagram social media marketing and electronic word of mouth on purchasing decisions at Gartenhutte café Mojokerto. The research approach was carried out quantitatively. Researchers used questionnaires, interviews and observations to collect research data. This research used purposive sampling to obtain 100 consumer respondents at the Gartenhutte Mojokerto cafe. The data obtained were analyzed using multiple linear regression methods and hypothesis testing. Analysis of these data illustrates that social media marketing and electronic word of mouth variables have a significant influence on purchasing decisions at Gartenhutte café Mojokerto. The coefficient of determination of 0.625 shows that marketing using these two methods influences purchasing decisions by 62.5% while the remaining 37.5% represents other influential factors which are not discussed in this research. Based on this evidence, researchers suggest that companies maximize uploaded content to interact more with consumers and increase the use of Instagram social media for promotions so that it is discussed more often by the public.